2011
DOI: 10.1371/journal.pone.0027627
|View full text |Cite
|
Sign up to set email alerts
|

Defects of Protein Phosphatase 2A Causes Corticosteroid Insensitivity in Severe Asthma

Abstract: BackgroundCorticosteroid insensitivity is a major barrier of treatment for some chronic inflammatory diseases, such as severe asthma, but the molecular mechanism of the insensitivity has not been fully elucidated. The object of this study is to investigate the role of protein phosphate 2A (PP2A), a serine/threonine phosphatase, on corticosteroid sensitivity in severe asthma.Methodology/Principal FindingsCorticosteroid sensitivity was determined by the dexamethasone ability to inhibit TNFα-induced IL-8 or LPS-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 31 publications
(41 reference statements)
7
84
1
2
Order By: Relevance
“…may also be at play in GR. In fact, recent work has shown that phosphorylation of the AF1 region of the NTD can also be used to tune the activity of GR (52), thus demonstrating that many of the same thermodynamic strategies utilized for signal propagation in folded proteins can also be applied to ID proteins. How classical and ID domain-mediated allosteric strategies combine to explain the complex regulation of GR controlled genes is an intriguing and as yet unanswered question.…”
Section: Discussionmentioning
confidence: 99%
“…may also be at play in GR. In fact, recent work has shown that phosphorylation of the AF1 region of the NTD can also be used to tune the activity of GR (52), thus demonstrating that many of the same thermodynamic strategies utilized for signal propagation in folded proteins can also be applied to ID proteins. How classical and ID domain-mediated allosteric strategies combine to explain the complex regulation of GR controlled genes is an intriguing and as yet unanswered question.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy transcripts in these categories/pathways included casein kinase 1, epsilon (CSNK1E) (64), mitogenactivated protein kinase 6 (MAPK6; a.k.a. ERK3) (65), mechanistic target of rapamycin (serine/threonine kinase) (MTOR) (66), oncostatin M (OSM) (67,68), TLR6 (69), mucin 20 (MUC20) (70,71), MAD homolog 1 (SMAD1) (72, 73), (74,75), claudin 3 (CLDN3), CLDN4, CLDN5, CLDN7 (76)(77)(78), and lethal giant larvae homolog 2 (Drosphila) (LLGL2) (79,80).…”
Section: Transcriptomic Analysismentioning
confidence: 99%
“…Altered PP2A activity plays a key role in cancer (3), neurodegenerative diseases (4), and innate immune responses (5). In the lung, PP2A is a key modulator of inflammatory responses in asthma (6) and chronic obstructive pulmonary disease (COPD) (5). Despite its importance in these and other biological processes, the mechanisms by which PP2A is regulated within the lung remains to be determined.…”
mentioning
confidence: 99%